The effectiveness of the communication program "No Hajj (pilgrimage) without a permit" - Al Shiban, Ali Mohammed; Abu Zenadah, Zamil Abbas (Journal of Humanities & Social Sciences, 2020)
This study aimed to evaluate the media campaign of the Ministry of the Interior of Saudi Arabia (no pilgrimage without permission) which directed to reducing overcrowding, and pressure on the custodian of the Two Holy Mosques from the point of view of the pilgrims inside and to know the importance of media campaigns and awareness programs in the formation of trends and behaviors related to the subject of the study. The study was based on a descriptive survey approach to achieve its objectives. This method was applied by simple random sampling. The sample of the study consisted of (262) participants, from pilgrims inside the Hajj season (2018). The study adopted the questionnaire as a tool for collecting information from the study sample. The study found many results, the most important of which is that the level of knowledge of pilgrims inside the program "No Hajj without a permit" is high (66.53%) and that text messages (SMS) were the most important means used to raise awareness of the concept of the campaign. The results also showed that the degree of acceptance of the sample of the pilgrims inside the letters of the campaign is not Hajj without a high permit, with an average of (3.43) and a standard deviation (0.84). Based on the findings of the study, researcher recommended a number of recommendations, the most important of which are: the need to pay attention to how to prepare and plan such campaigns and attention to the nature of their messages, and the need to study the target audience which represents the ultimate goal of any media awareness work, and to benefit from the social networks in communication with the public.